A systematic review of published interventions for primary and secondary prevention of ischaemic heart disease (IHD) in rural populations of Australia. (December 2016) - Alston, Laura; Peterson, Karen; Jacobs, Jane; Allender, Steven; Nichols, Melanie
Abstract Background Rural Australians are known to experience a higher burden of ischaemic heart disease (IHD) than their metropolitan counterparts and the reasons for this appear to be highly complex and not well understood. It is not clear what interventions and prevention efforts have occurred specifically in rural Australia in terms of IHD. A summary of this evidence could have implications for future action and research in improving the health of rural communities. The aim of this study was to review all published interventions conducted in rural Australia that were aimed at the primary and/or secondary prevention of ischaemic heart disease (IHD) in adults. Methods Systematic review of the peer-reviewed literature published between January 1990 and December 2015. Search terms were derived from four major topics: (1) rural; (2) ischaemic heart disease; (3) Australia and; (4) intervention/prevention. Terms were adapted for six databases and three independent researchers screened results. Studies were included if the published work described an intervention focussed on the prevention or reduction of IHD or risk factors, specifically in a rural population of Australia, with outcomes specific to participants including, but not limited to, changes in diet, exercise, cholesterol or blood pressure levels. Results Of 791 papers identified in the search, seven studies met the inclusion criteria, and one further study was retrieved from searching reference lists of screened abstracts. Typically, excluded studies focused on cardiovascular diseases without specific reference to IHD, or presented intervention results without stratification by rurality. Larger trials that included metropolitan residents without stratification were excluded due to differences in the specific needs, characteristics and health service access challenges of rural populations. Six interventions were primary prevention studies, one was secondary prevention only and one included both primary and secondary intervention strategies. Two interventions were focussed exclusively on Aboriginal and Torres Strait Islander (Australian Indigenous) populations. Conclusions Few interventions were identified that exclusively focussed on IHD prevention in rural communities, despite these populations being at increased risk of IHD in Australia, and this is consistent with comparable countries, internationally. Although limited, available evidence shows that primary and secondary interventions targeted at IHD and related risk factors can be effective in a rural setting.